All-Union Society of Inventors and Innovators in System of State Policy, Aimed at Accelerating Scientific-Technical Progress in the Late 1950’s - Early 1960-ies (by Example of Activities of AUSII Tatar Regional Council) - D. A. Pinayeva (Научный диалог)
The article is devoted to the activities of the Tatar regional branch of the all-union society of inventors and innovators (AUSII) in the context of the implementation of scientific and technical policy of the state aimed at accelerating scientific-technical progress. The main sources of work are published party and government documents, materials from the Fund of the all-Union Central Council of trade unions (AUCCTU), State archive of the Russian Federation, as well as documents from the National archives of the Republic of Tatarstan introduced into scientific circulation for the first time. The research indicates that a characteristic of scientific and technical policy of the USSR from the second half of 1950-ies becomes the forming of a centralized system of management of scientific-technical progress. The mobilization model of development involved the creation of conditions to enable a greater number of employees in scientific and technical creativity, so the special place in the scientific and technical infrastructure was given to the scientific and technical unions, formally bearing a public character, such as scientific-technical society (STS), AUSII, etc., the general management of which was entrusted to AUCCTU. Special attention is paid to the analysis of structural and functional features of AUSII. It is indicated that the popular idea of creating a mass organization aimed at promoting inventive and innovative activity of the broad masses of workers could not be effectively implemented due to a number of circumstances, such as lack of autonomy in the choice of strategy of development of the organization, the lack of an effective system of communication between the links of the inventive process, the lack of effective controls. It is concluded that, despite some positive aspects in enhancing invention and innovation in the Tatar ASSR, the AUSII regional Council could not deal with the root problems: lack of the exchange of experience, slow implementation of innovations in production, numerous violations of the law against the innovators and inventors.